INOVASI SISTEM INFORMASI TENAGA KESEHATAN (SINAKES) ONLINE PADA DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU KOTA SEMARANG - Nurul Lutfiana; Endang Larasati (Journal of Public Policy and Management Review, 2019)
The government which is responsible for implementing the State is required to improve the quality of public services so that the fulfillment of community needs can run well. One way the government can escalate this quality of public services is by creating an innovation. As an effort to improve public services in the field of licensing of health personnel, DPM-PTSP Semarang established a "SINAKES" Online Innovation. This study utilizes the Innovation Attribute theory of SINAKES Online and the theory of Driving Factors and Obstacles to Innovation in the Public Sector, which owned by Rogers and Albury. The results of this study show that SINAKES Online Innovation has relative advantages, suitabilities, complexities, possibilities to try and simplicities to observe. SINAKES Online Innovation has various driving factors, namely, the desire to change for the better, the availability of facilities and infrastructure, and supportive surroundings. However, there are also several inhibiting factors, such as short-term budgets and planning and excessive dependence on high performers. Therefore, to optimize the implementation of SINAKES Online, we need to specifically allocate budgets for its development and IT development training for employees such as holding workshops.